PENGARUH SISTEM INFORMASI TEKNOLOGI ELEKTRONIK ATAS TASK PERFORMANCE AUDITOR KANTOR AKUNTAN PUBLIK BIG 4 - Herusetya, Antonius (UI Scholars Hub, 2010)
Auditors of public accounting firms frequently deal with the tasks oriented to the audit judgment decision makings. And due to the nature of these tasks are frequently complex and unstructured, they need electronic technology based information system to achieve higher audit quality and to minimize audit risks. The purpose of this study is to examine whether the information system used by the auditors of public accounting firms in the form of Group Support Systems (GSS), Group Decision Support Systems (GDSS) or other electronic information technology software could increase auditors’ performance in their audit tasks. With the respondent of practicing auditors from the Big 4 public accounting firms in Indonesia, and by using structural equation model (SEM) analysis, we found evidence that the usage of Electronic Information System Technology (EIST) has significantly positive impact on audit task performance. We found evidence that the perceived ease of use from the Big 4 auditors has positive significant impact on the perceive usefulness of electronic information system technology adopted by public accounting firms. We have also found evidence that the nature of critical, judgmental, and non-routine audit task complexities in the audit fields has significant impact on the system usage. On the other hands the perceived of ease of use, and the perceived usefulness of electronic information system technology have weak significant impact on the system utilization of the Big 4 auditors.